Workers' compensation insurer risk control systems: Opportunities for public health collaborations. (September 2018) - Moore, Libby L.; Wurzelbacher, Steven J.; Shockey, Taylor M.
Abstract: Introduction: Workers' compensation (WC) insurers offer services and programs for prospective client selection and insured client risk control (RC) purposes. Toward these aims, insurers collect employer data that may include information on types of hazards present in the workplace, safety and health programs and controls in place to prevent injury/illness, and return-to-work programs to reduce injury/illness severity. Despite the potential impact of RC systems on workplace safety and health and the use of RC data in guiding prevention efforts, few research studies on the types of RC services provided to employers or the RC data collected have been published in the peer-reviewed literature. Methods: Researchers conducted voluntary interviews with nine private and state-fund WC insurers to collect qualitative information on RC data and systems. Results: Insurers provided information describing their RC data, tools, and practices. Unique practices as well as similarities including those related to RC services, policyholder goals, and databases were identified. Conclusions: Insurers collect and store extensive RC data, which have utility for public health research for improving workplace safety and health. Practical applications: Increased public health understanding of RC data and systems and an identification of key collaboration opportunities between insurers and researchers will facilitate increased use of RC data for public health purposes. Highlights: Insurers provided safety, ergonomics, and industrial hygiene service to insureds. Risk control (RC) consultants collected insureds' safety program and exposure data. Most RC departments used databases that enabled electronic forms and data storage. Insurers used coverage requirements and incentive strategies to minimize injuries. RC consultation provides public health partnership opportunities.